Peran Program Literasi Sekolah terhadap Peningkatan Minat Baca Siswa MI Miftahussholihin Martapura - Husnul Hatimah; Ahmad Mahfuz (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to describe the role of the school literacy program in increasing student reading interest at MI Miftahussholihin Martapura, stemming from the low reading interest among elementary students. Utilizing a qualitative approach with a case study design, data were collected through in-depth interviews, observation, and documentation from the principal, teachers, and students (purposive sampling), and then analyzed using the interactive model of Miles and Huberman. The research findings indicate that the school literacy program plays a significant role in increasing student reading interest through reading habituation, provision of engaging literacy facilities, and full support from the school community. Although constraints such as limited reading collections and insufficient parental assistance at home were encountered, the study concludes by emphasizing the importance of continuous collaboration for the program's success.